The Impact of Competency-Based Training Towards Technical Skills Mastery Among Vocational Education Students - Masran, Saiful Hadi; Zulkiffle, Muhammad Hafizul Iskandar; Hasan, Azman; Yamaguchi, Shinobu Yume; Marian, Fairuz (Journal of Technical Education and Training, 2025)
Technical skills are essential for success in various professional fields, playing a crucial role in ensuring job readiness and adaptability. This study investigates the impact of Competency-Based Training (CBT) on the technical skills mastery of final-year vocational education students at a public university in Malaysia, focusing on three mechanical programs: General Machining, Welding and Metal Fabrication, and Refrigeration and Air Conditioning. Using a quantitative research design, the study surveyed 115 students to assess their perceptions of proficiency in key technical skills, including technical communication, analytical, computer, and practical skills. The results indicate that students generally exhibit high levels of competence across most technical areas, particularly in Technical Drawing, Workshop Safety, and Technical Communication, suggesting the effectiveness of CBT in aligning educational outcomes with industry needs. However, areas such as Blueprint Reading and Quality Control were identified as needing improvement. The findings underscore the importance of continuous curriculum enhancements to address specific skill gaps and ensure that graduates are well-prepared to meet the evolving demands of the workforce.